What cortical areas are responsible for blindsight in hemianopic patients?. (November 2020) - Sanchez-Lopez, Javier; Cardobi, Nicolò; Pedersini, Caterina A.; Savazzi, Silvia; Marzi, Carlo A.
Abstract: The presence of above-chance unconscious behavioral responses following stimulus presentation to the blind hemifield of hemianopic patients (blindsight) is a well-known phenomenon. What is still lacking is a systematic study of the neuroanatomical bases of two distinct aspects of blindsight: the unconscious above chance performance and the phenomenological aspects that may be associated. Here, we tested 17 hemianopic patients in two tasks i.e. movement and orientation discrimination of a visual grating presented to the sighted or blind hemifield. We classified patients in four groups on the basis of the presence of above chance unconscious discrimination without or with perceptual awareness reports for stimulus presentation to the blind hemifield. A fifth group was represented by patients with interruption of the Optic Radiation. In the various groups we carried out analyses of lesion extent of various cortical areas, probabilistic tractography as well as assessment of the cortical thickness of the intact hemisphere. All patients had lesions mainly, but not only, in the occipital lobe and the statistical comparison of their extent provided clues as to the critical anatomical substrate of unconscious above-chance performance and of perceptual awareness reports, respectively. In fact, the two areas that turned out to be critical for above-chance performance in the discrimination of moving versus non-moving visual stimuli were the Precuneus and the Posterior Cingulate Gyrus while for perceptual awareness reports the crucial areas were Intracalcarine, Supracalcarine, Cuneus, and the Posterior Cingulate Gyrus. Interestingly, the proportion of perceptual awareness reports was higher in patients with a spared right hemisphere. As to probabilistic tractography, all pathways examined yielded higher positive values for patients with perceptual awareness reports. Finally, the cortical thickness of the intact hemisphere was greater in patients showing above-chance performance than in those at chance. This effect is likely to be a result of neuroplastic compensatory mechanisms.